Analisa Pengaruh Budaya Organisasi dan Knowledge Sharing terhadap Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Mataram - Novinaz Benita (Jurnal Riset Akuntansi, 2020)
Performance indicators are very important in realizing good and transparent governance. In addition, performance indicators also support the government tasks in providing the best service to the community adopt to the characteristics as public organization, which is oriented to public services. Organizational culture provides support for members in improving their abilities through knowledge sharing in discussion groups. Furthermore, knowledge sharing increases understanding among members so that they support one another and improve performance, and ultimately find the best work processes for the organization. This type of research is an explanatory research and used quantitative data analysis techniques. This study analyzed how organizational culture and knowledge sharing affected to employee performance, especially in the Investment and one-stop integrated service office in Mataram City. The result described organizational culture variables had a significant and positive effect on employee performance. Meanwhile, knowledge sharing variable showed that knowledge sharing was not significantly influenced to employee performance. Those findings were expected to provide insight for officials in the Investment and one-stop integrated service office in order to improve the performance of their employees in improving the quality of services of the public organization itself.